2013
DOI: 10.1097/ans.0b013e3182902020
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Testing of an Instrument Measuring Core Competencies of Nursing Students

Abstract: Assessing the core competencies of nursing students provides information about students' learning outcomes for educational evaluation and improvement. The aim of this study was to develop the Nursing Students Core Competencies scale to measure 8 core competencies of nursing students in Taiwan. The study employed factor analysis and Mokken scaling analysis for psychometric testing of this instrument between a group of nursing graduates and their evaluators. The results indicated that the Nursing Students Core C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 17 publications
1
20
0
5
Order By: Relevance
“…Of the 19 studies included in this review, four were conducted in the United States and in Taiwan, two in Sweden and Iran, and one study each in the UK, Ireland, Australia, Canada, Korea, Iran and Finland . The studies have their origin in different countries and educational paradigms and show a big variation of methods and designs (see Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 studies included in this review, four were conducted in the United States and in Taiwan, two in Sweden and Iran, and one study each in the UK, Ireland, Australia, Canada, Korea, Iran and Finland . The studies have their origin in different countries and educational paradigms and show a big variation of methods and designs (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The methodological approaches differ from quantitative ( n = 11), qualitative ( n = 5) to mixed methods ( n = 3). Data were collected by questionnaires in 12 studies, by questionnaires combined with focus groups in two studies, by focus group interviews in two studies, and by observations, video analysis combined with questionnaire/checklist and interviews in one study. In addition to Walsh et al ., three other articles included instrument development and validation .…”
Section: Resultsmentioning
confidence: 99%
“…Patient education is a key attribute of patient-centred care (Kitson et al, 2012;Pelzang, 2010). This is supported in other studies citing patient education as a crucial nursing activity and is globally understood to be a core competency for entry-level practice nurses Brown & Crookes, 2016a;Ivarsson & Nilsson, 2009;Nilsson et al, 2014;Perng & Watson, 2013).…”
Section: Patient-centred Care Of Newly Graduated Nursesmentioning
confidence: 87%
“…Although this scale falls within the ordinal level of measurement (Cohen et al, 2013;Furr & Bacharach, 2008), several studies found that parametric methods could be utilised together for data analysis (Allen & Seaman, 2007;Norman, 2010). The points, therefore, were labelled with a continuous line, which yielded a continuous interval measure (Allen & Seaman, 2007;Perng & Watson, 2013). Table 5 Bondy's Modified Criteria Used to Classify Student Competence (Brown & Crookes, 2016) Refers to being safe and knowledgeable most of the time; skilful in parts.…”
Section: Research Guide Questionsmentioning
confidence: 99%
See 1 more Smart Citation